不同分层方法对早期弥漫大B细胞淋巴瘤预后价值的比较 (Zhonghua Xue Ye Xue Za Zhi, 2016)
OBJECTIVE: To compare the prognostic value of different models in patients with early-stage diffuse large B-cell lymphoma (DLBCL). METHODS: Early-stage DLBCL patients diagnosed from January 2000 to December 2012 were analyzed retrospectively. All patients received with at least 2 cycles of immunochemotherapy R-CHOP regimen (rituximab, cyclophosphamide, doxorubicin, vincristine, prednisone) with or without radiotherapy. The prognostic value of international prognostic index (IPI), revised IPI (R-IPI) and enhanced IPI (NCCN-IPI) was compared. RESULTS: Ninety-seven cases of early-stage DLBCL were included in the study. The median age was 58 years (15–88 years) with a median follow-up of 34.7 months (range 7.3–77.4 months). The expected 5-year overall survival (OS) for entire group was 82%. There was no patient in the high risk group according to IPI or NCCN-IPI. According to IPI, the 5-year OS in the low, low intermediate, high intermediate risk groups were 95%, 38% and 60%, respectively. According to R-IPI, the 5-year OS in the very good, good, and poor risk groups were 93%, 75% and 60%, respectively. According to NCCN-IPI, the 5-year OS in the low, low intermediate, high intermediate risk groups were 92%, 85% and 29%, respectively. CONCLUSION: NCCN-IPI would be of an ideal prognostic model for early-stage DLBCL patients.